Agronomic Cultivation, Chemical Composition, Functional Activities and Applications of Pereskia Species – A Mini Review - Maciel, Vinicius B.V.; Yoshida, Cristiana M.P.; Goycoolea, Francisco M. (Current Medicinal Chemistry, 2019)
Background: The exploration of the plant biodiversity as a natural source to obtain sustainable food products and new bioactive pharmaceutical compounds has been growing significantly due to their abundance, safety and economy. Natural pharmaceutical and edible compounds present some advantages when compared to synthetic ones, such as being chemically inert and widely available. In this sense, plants of the genus Pereskia belonging to the Cactaceae family, have been studied. It is an unconventional wild edible plant that contains a large amount of protein and minerals. Studies have demonstrated their biological activities and potential application in different areas such as pharmaceutical, medicinal and food. Objective: This review is focused on the chemical composition, functional properties, applications on pharmaceutical, nutraceutical and food areas and formulation techniques to enhance the stability and bioavailability of bioactive compounds from the underutilized wild edible plant known as ora-pro-nobis (Pereskia aculeata or Pereskia grandifolia). Conclusion: The latest studies involving ora-pro-nobis demonstrated its great potential due to its biological activities, which could stimulate further investigations. The utilization of this plant as a natural source to supplement the diet, or to prepare new food products and pharmaceutical formulations is an attractive approach to explore and fully realize the potential of the rich biodiversity found in Brazil and in other countries.
Keywords: unconventional plant